Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Return on Assets pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2020-2024 - Alda Damayanti; Andi Arifwangsa Adiningrat; Firman Syah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study uses a quantitative approach with an explanatory causal design. The sample was determined using purposive sampling techniques and obtained 18 companies from a total population of approximately 83, resulting in 90 observation units. The data used were audited annual financial reports. The analysis was performed using multiple linear regression. The results show that (1) Current Ratio and Debt to Equity Ratio partially have a negative significant effect on Return on Assets. (2) Simultaneously, Current Ratio and Debt to Equity Ratio also have a significant effect on Return on Assets. These findings indicate that liquidity management and capital structure play an important role in determining a company's profitability.